Identification of Earthquake Hazard Vulnerability in Bengkaung Village, West Lombok Using Geomagnetic Methods - Muhammad Amin; Hiden Hiden; Suhayat Minardi (Postgraduate, University of Mataram, 2022)
An earthquake disaster is an event that causes various damage and loss of life. This study aims to determine the vulnerability of earthquake hazards in Bengkaung Village, West Lombok Regency. The method used in this research is the geomagnetic method. The results of this: study indicates the value of the magnetic field anomaly in the range of -1100 nT-1500 nT. 2D modeling with 4 paths shows that the study area is dominated by 5 rock layers with a susceptibility range between (0.013 - 6.21)Ã—10^(-3) in SI, which consists of sandstone, clay, fractured andesite lava, fresh andesite lava. and granite. The highest vulnerability to earthquake hazards is in the southern part of Bengkaung Village, due to the presence of a cohesive soil type (like clay) on the surface of the study area, coupled with the presence of intrusions and faults. Meanwhile, the western part of Bengkaung Village and the northern part of the Bengkaung area have a relatively smaller earthquake hazard vulnerability than the southern part. This is because the western and northern parts have the main layer of non-cohesive soil (sandstone) which has high shear strength and becomes a damper in wave propagation when an earthquake occurs